Kasztelan krakowski Jerzy ks. Zbaraski (1574-1631). Szkic do portretu antyregalisty - Anusik, Zbigniew (Przegląd Nauk Historycznych, 2010)
Jerzy prince Zbaraski was a descendent of the rich and powerful magnates family. He was born in 1574 as a son of Janusz prince Zbaraski (d. 1608) voivode of Bracław and Anna princess Czetwertyńska. Well educated, very good at foreign languages after long studies abroad, as a young man, together with his younger brother – prince Krzysztof (1579-1627), he became a king’s courtier. A conflict between him and Jesuits at the court was a cause of his disgrace. Passed over by the king in the distribution of state offices and crown estates, he became an oppositionist. Since then Zbaraski brothers fought internal and foreign policy of the king. After the death of their father, prince Jerzy and prince Krzysztof belonged to the exclusive group of the richest Crown magnates. Both of them played a great political role during the reign of Zygmunt III. As a castellan of Kraków (since 1620) prince Jerzy felt himself authorized to review and criticize almost every move of the king. Not until the Swedes invaded Prussia, prince castellan noticed the necessity of deep state reforms. After death of the younger brother, the only heir of the huge family landed estates was prince Jerzy. Because of his fortune the castellan of Kraków was the second Crown magnate of his times. During the last years of his life he played a first role on the political scene of the Republic. Prince Jerzy was very popular among Polish nobility. He was regarded as an ideal senator. He enjoyed widespread support. He was also admired and widely revered. Jerzy prince Zbaraski died in Kraków July 30th 1631 as a last male descendent of his family.